Effect of isotretinoin on myopia and axial length: a pilot study. (1st October 2020) - Yasar, Erdogan; Gurlevik, Ugur; Kemeriz, Funda; Atalay, Eray
Abstract: Purpose: To investigate the effect of oral isotretinoin use on refractive error, axial length, and anteroposterior segment parameters. Materials and methods: In this prospective study, 50 eyes of 50 patients using isotretinoin with a diagnosis of acne vulgaris and 50 eyes of 50 healthy control subjects were included. After detailed biomicroscopy, measurements were taken of axial length, lens thickness, central corneal thickness, anterior chamber depth, central retinal thickness, and subfoveal choroidal thickness. The pupils of both eyes were dilated with one drop of cycloplegic drops after refraction measurement. Visual acuity examination was performed with a Snellen chart the next day. The same procedure was repeated at the end of the third and sixth month of drug treatment. Results: Forty-seven patients with acne vulgaris and 45 healthy controls met the inclusion criteria and were included in the analysis. The mean ages of the patients and the controls were 21.7 ± 2.5 years (range, 18–28 years) and 22.6 ± 2.7 years (range, 19–27 years), respectively. No significant changes were observed in any parameters in the third and sixth month in the control group ( p  > 0.05). The most important result was significant increases in myopia and axial length in the sixth month of isotretinoin use ( p  = 0.01, p  = 0.04, respectively). There were no significant relationships between increases in myopia and axial length and patients' age, sex, drug dose, and initial refraction ( p  > 0.05). The changes in spherical equivalent and axial length differed significantly between the drug group and the control group ( p  = 0.001, p  = 0.001, respectively). Conclusions: Isotretinoin is one of the important molecules in the aetiology of myopia. Oral isotretinoin treatment may increase myopia and axial length, although not to a clinically significant degree. However, as this was a pilot study, there is a need for further studies with more patients and longer follow-up periods.